Meningkatkan Keterampilan Kritik Seni Peserta Didik Kelas X MIPA 4 Pada Karya Seni Rupa Dua Dimensi Dalam Pelaksanaan Pembelajaran Dari Rumah Sekolah Menengah Atas Negeri 1 Muaro Jambi Tahun Pelajaran 2020/2021 - Emri Yasmen (STIT Muhammadiyah Paciran Lamongan, 2021)
Art criticism skills are one of the critical thinking skills that are continuously improved in class X MIPA4 students of SMAN 1 Muaro Jambi in the 2020/2021 academic year towards an object of two-dimensional art work through learning activities from home, using the google classroom application. The art criticism skills of class X MIPA4 students at SMAN 1 Muaro Jambi in the 2020/2021 school year are still low, not in accordance with the indicators of success, so it is necessary to take action using the classroom action research method by designing learning steps according to the application used in learning from home and the picture and picture method. This research was conducted in two cycles in February and March 2021, where each cycle consisted of two meetings. The results showed that there was an increase in the achievement of each variable and stage of art criticism that had been determined. There was a significant increase between 9% to 22% in each variable and stage of art criticism, even the variable of communicating art criticism through writing in the descriptive stage of class X MIPA4 students at SMAN 1 Muaro Jambi in the 2020/2021 school year experienced a very significant increase up to 78 .12%.